Effectiveness of Risk Management through Risk Maturity Measurement: A Study at PT Pelabuhan Indonesia - Utami, Lestari; Djunita Pasaribu, Rina (Publisher Cv. Inara, 2024)
Research aims: This study aims to evaluate the effectiveness of risk management at Pelindo post-merger and measure its risk management maturity level. Moreover, the study intends to offer relevant recommendations for the company in developing risk management strategies and implementation. Design/Methodology/Approach: This study adopts a qualitative descriptive approach with a case study strategy, wherein the researcher analyzes an organization as the unit of analysis in a non-contrived setting, reflecting a natural environment without manipulation. Data collection techniques include interviews and document analysis, while data analysis follows the Miles and Huberman model with four main components: data collection, data reduction, data presentation, and conclusion drawing. Research findings: The study's findings indicate that the risk management maturity level at Pelindo post-merger is at the good practice phase, scoring 2.94 from the dimension and performance aspects assessment. Recommendations for improvement include enhancing risk culture, improving the effectiveness of risk management functions, and aligning risk strategy with the ERM transformation plan to increase the effectiveness and compliance of risk management. Theoretical Contribution/Originality: This research makes a theoretical contribution by assessing the level of risk management maturity in the context of mergers among state-owned enterprises (SOEs) in Indonesia's maritime industry. It uses measurement methods tailored to regulations from the Ministry of SOEs, providing a reference for other companies seeking to develop effective risk management strategies. Practitioners/Policy Implications: This research suggests that organizations should strengthen risk culture responsibilities in job descriptions at all levels, as well as adopt technology and automation for real-time risk monitoring to enhance risk management effectiveness and ensure alignment with corporate strategy. Research Limitations/Implications: The limitations of this study primarily stem from restricted access to internal and sensitive data, which constrains the depth of analysis and hampers comparison with industry best practices.